2004
DOI: 10.1191/0961203304lu2035oa
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine, antiphospholipid antibodies and risk of thrombosis in patients with systemic lupus erythematosus

Abstract: Cardiovascular disease is a major cause of morbidity and mortality in patients with systemic lupus erythematosus (SLE). Antiphospholipid syndrome (APS) is one of the most important causes of thrombosis in SLE. In addition, an association between hyperhomocysteinemia and increased cardiovascular risk has also been reported. Our aim is to analyse the association of thrombosis with plasma total homocysteine (ptHcy), antiphospholipid antibodies (aPL) and other vascular risk factors in SLE patients. Fasting plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
2
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 32 publications
2
20
2
2
Order By: Relevance
“…Similarly, previous smoking history and other important risk factors for arterial vascular events such as dyslipidemia (10), diabetes mellitus, and serial high-sensitivity C-reactive protein levels (24;40) were not available uniformly in all patients. Systematic evaluation of these factors and thrombophilic risk factors such as hyperhomocysteinemia (15;21;23), antiprothrombin antibodies (17;58) and other inherited and acquired thrombophilic conditions (59) is an important future goal. Nonetheless, we have identified important factors contributing to the development of arterial vascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, previous smoking history and other important risk factors for arterial vascular events such as dyslipidemia (10), diabetes mellitus, and serial high-sensitivity C-reactive protein levels (24;40) were not available uniformly in all patients. Systematic evaluation of these factors and thrombophilic risk factors such as hyperhomocysteinemia (15;21;23), antiprothrombin antibodies (17;58) and other inherited and acquired thrombophilic conditions (59) is an important future goal. Nonetheless, we have identified important factors contributing to the development of arterial vascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Patri et al2 reported that patients with SLE were more likely to have a sedentary lifestyle, obesity, and hypercholesterolemia, while Borha et al7,8 found that, compared with controls, patients with SLE had lower high-density lipoprotein (HDL) cholesterol as well as higher very low-density lipoprotein (VLDL) cholesterol, triglycerides, and lipoprotein (a) concentrations. Increased carotid intima thickness, increased plasma concentrations of circulating oxidized LDL and homocysteine, as well as endothelial defects, have all been incriminated in the premature coronary heart disease seen in patients with SLE 911…”
Section: Introductionmentioning
confidence: 99%
“…Generally, homocysteine is considered as a prothrombotic factor in other rheumatologic diseases, but there are still some controversial reports. 32 Due to the above limitations in our study, we recommend longitudinal studies on hyperhomocysteinemia and clinical thrombosis stratified by presence or absence of HLA-B51 and on other ethnic populations with larger case groups to confirm the finding. 28 Other studies reported that high serum homocysteine level is an independent risk factor for thrombosis in patients with systemic lupus erythematous, 29,30 but some other studies have reported that even severe hyperhomocysteinemia, in itself, is not sufficient to promote thrombosis and rather, other factors associated with abnormal homocysteine metabolism may be responsible for the propensity to thrombosis observed in individuals with severe hyperhomocysteinemia 31 and suggested that the role of homocysteine as a marker of vascular risk may depend on the presence of traditional risk factors of thrombosis, although a modest intrinsic effect cannot be entirely excluded.…”
Section: Discussionmentioning
confidence: 66%
“…28 Other studies reported that high serum homocysteine level is an independent risk factor for thrombosis in patients with systemic lupus erythematous, 29,30 but some other studies have reported that even severe hyperhomocysteinemia, in itself, is not sufficient to promote thrombosis and rather, other factors associated with abnormal homocysteine metabolism may be responsible for the propensity to thrombosis observed in individuals with severe hyperhomocysteinemia 31 and suggested that the role of homocysteine as a marker of vascular risk may depend on the presence of traditional risk factors of thrombosis, although a modest intrinsic effect cannot be entirely excluded. 32 Due to the above limitations in our study, we recommend longitudinal studies on hyperhomocysteinemia and clinical thrombosis stratified by presence or absence of HLA-B51 and on other ethnic populations with larger case groups to confirm the finding. It also would be worthwhile to study other genotypes involved in the pathway of homocysteine metabolism which has been reported to be associated with hyperhomocysteinemia in other populations.…”
Section: Discussionmentioning
confidence: 66%